Analisis Dasar Pertimbangan Majelis Hakim Atas Tindak Pidana Anak Yang Dilakukan Secara Bersama Ditinjau Dari Teori Keadilan (Studi Putusan Pengadilan Negeri Kayu Agung Nomor 9/Pid.Sus-Anak/2023/PN Kag) - Wijaya, Andy; Zahri, Saipudin; Salia, Erli (Lex Stricta : Jurnal Ilmu Hukum, 2025)
Children who commit crimes must still be treated humanely by upholding the principles of non-discrimination, the best interests of the child, and respect for their right to life and development. This study examines the basis for the panel of judges' considerations regarding criminal acts committed by children jointly from the perspective of justice theory through a study of Kayu Agung District Court Decision Number 9/Pid.Sus-Anak/2023/PN Kag, as well as the legal remedies filed by the defendant against the decision. The method used is normative legal research supported by field data and is descriptive and analytical in nature. The results of the study show that the judges' considerations were based on philosophical aspects that emphasized rehabilitation for the defendants, thus reflecting the application of modern criminal law theory and some modern theories of justice. However, the defendants filed an objection because they considered that the verdict did not fully take into account mitigating factors, such as their confession and remorse for their actions, so the judges should have given more consideration to these factors before handing down the verdict.